2009
DOI: 10.1029/2008jd010884
|View full text |Cite
|
Sign up to set email alerts
|

Rapid aerosol particle growth and increase of cloud condensation nucleus activity by secondary aerosol formation and condensation: A case study for regional air pollution in northeastern China

Abstract: [1] This study was part of the international field measurement Campaigns of Air Quality Research in Beijing and Surrounding Region 2006 (CAREBeijing-2006). We investigated a new particle formation event in a highly polluted air mass at a regional site south of the megacity Beijing and its impact on the abundance and properties of cloud condensation nuclei (CCN). During the 1-month observation, particle nucleation followed by significant particle growth on a regional scale was observed frequently ($30%), and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
177
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(195 citation statements)
references
References 49 publications
16
177
1
1
Order By: Relevance
“…Reduced hygroscopicity of newly formed particles can be expected where SOA plays a major role in particle growth, e.g., over boreal and tropical forests [Tunved et al, 2006;Gunthe et al, 2009]. In other regions, such as polluted megacities, high proportions of inorganic compounds may enhance the hygroscopicity of CCN [Wiedensohler et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced hygroscopicity of newly formed particles can be expected where SOA plays a major role in particle growth, e.g., over boreal and tropical forests [Tunved et al, 2006;Gunthe et al, 2009]. In other regions, such as polluted megacities, high proportions of inorganic compounds may enhance the hygroscopicity of CCN [Wiedensohler et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Ambient measurements and modeling studies suggest that nucleated particles can grow into the size range of cloud condensation nuclei (CCN) in various environments ranging from remote continental to highly polluted [Kerminen et al, 2005;Laaksonen et al, 2005;Pirjola et al, 2002;Wang and Penner, 2009;Kuang et al, 2009;Wiedensohler et al, 2009]. Recently, it has been proposed that nucleation of new particles happens by activation of thermodynamically stable clusters that are either charged [Horrak et al, 1998;Kulmala et al, 2000;Yu and Turco, 2008] or neutral [Kulmala et al, 2007], and continually present in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…reported that the GR of sulfur-poor NPF was on average about 80 % larger than that of sulfur-rich NPF, and that the NPF events increased CCN by 0.4-6 times in Beijing, where various source apportionments of PM 2.5 were reported by Zhang et al (2013). Wiedensohler et al (2009) found that the CCN size distribution is dominated by the growing nucleation mode in Beijing, which accounted for up to 80 % of the total CCN number concentration, in contrast to the usually found phenomenon of the dominance by the accumulation mode.…”
Section: Introductionmentioning
confidence: 99%
“…The newly formed particles from atmospheric nucleation are often able to grow into CCN size and further influence cloud properties or even global climate Laaksonen et al, 2005;Wiedensohler et al, 2009). Kerminen et al (2012) present a synthesis of our current (end of 2012) knowledge on CCN production associated with atmospheric nucleation, and conclude that CCN production associated with atmospheric nucleation is both a frequent and widespread phenomenon in numerous types of continental boundary layers, and probably also for a large fraction of the free troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…Also, primary and secondary particles undergo chemical and physical transformations and are subjected to cloud processing and transport in the atmosphere (8,9). The formation mechanisms leading to severe haze episodes with exceedingly high PM 2.5 levels in China remain highly uncertain, and the abundance and chemical constituents of PM 2.5 vary considerably, depending on complex interplay between meteorology, pollution sources, and atmospheric chemical processes (10)(11)(12)(13)(14)(15)(16). For example, on the basis of ambient measurements and receptor model analysis, the contribution to the annual mean PM 2.5 in Beijing has been suggested to be mainly from industrial pollution and secondary inorganic aerosol formation, but negligibly from traffic emissions (14).…”
mentioning
confidence: 99%